PENGARUH PEMBERIAN JUS KULIT MANGGIS TERHADAP KADAR LOW DENSITY LIPOPROTEIN (LDL) DAN HIGH DENSITY LIPOPROTEIN (HDL) MENCIT - Adhy Nugroho, Christianto (Widya Warta, 2018)
High level of fat in the body can cause various diseases. To reduce the fat content people made various attempts, for example, by having diet, doing regular excercise, or taking medicine. Plants are source of chemicals that are the basic ingredients of drugs. This research, therefore, was aimed to determine the effect of mangosteen peel juice on low density lipoprotein (LDL) and high density lipoprotein (HDL). Materials used for the research were mangosteen peels and animals test. The experiment was conducted by using an experimental method consisting of 4 treatments and 5 replications. Group 1 had no treatment, group 2 was given quail egg yolk, group 3 was given quail egg yolks and 200 g mangosteen peel juice, group 4 was given quail egg yolk and mangosteen juice of 300 gÂ  of mangosteen peel juice. The treatment was carried out for 14 days. The results showed that the LDL levelwas decreased while the HDL level increased.